LAND MANAGEMENT MECHANISM IN THE SYSTEM OF LAND RESOURCE MANAGEMENT: ROLE AND FUNCTIONS - Hreshchuk , Г. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2023)
The article delves into the land management mechanism within the general land management system to maximize the effective utilization of agricultural land, investment opportunities, and productivity potential in rural areas, and to create conditions for its social transformation into a powerful factor of economic growth. Given the state's sustainable development strategy for land use, the introduction of the land market, and the conceptual shift of community development to territorial and spatial planning, which is a crucial tool for land resource management, attention is focused on several tasks that must be accomplished to improve the land management mechanism in the general system of managing land resources in the agricultural sector. Specifically, it is necessary to guarantee the most efficient and ecologically safe use of all agricultural lands suitable for profitable production of agricultural products; create territorial conditions for the consolidation of land plots and better their use by implementing measures that ensure the preservation of lands and their involvement in agricultural production; restore disturbed and degraded lands and bring them to the conditions suitable for agricultural production, among others. In order to effectively implement certain actions, it is necessary to pass all stages of planning for the rational use and protection of agricultural land at a legislative level. This will help to formulate and set relevant requirements for land management regulations within defined territorial zones, including provisions regarding the use and possible changes of these rules. The land management mechanism plays a crucial role in the land management system by carrying out various functions. The tasks of agriculture in the implementation of the land management mechanism within the general system of land resource management in the agricultural sector are also clearly defined and formulated.